Palliative care in non-malignant disease. (December 2015) - Gadoud, A.C.; Johnson, M.J.
Abstract: A lack of access to specialist palliative care has led to a lack of clinicians' skills, knowledge and attitudes pertinent to the management of patients with chronic conditions such as end-stage heart failure, chronic obstructive pulmonary disease and renal failure. Recognition of the 'end stage' remains a key challenge. This article discusses how a palliative care approach can be incorporated into standard active treatment, outlines the management of important symptoms and discusses the importance of advance care-planning. The particular problems experienced by patients with chronic neurodegenerative disease are discussed, and swallowing and respiratory difficulties are explored in the context of potential loss of mental capacity and ability to communicate. The importance of excellent communication skills is highlighted in particular regard to advance planning for end-of-life issues.